Analysis of Segmentation, Targeting, and Positioning (STP) In Increasing Sales Volume At Imba Coffee Surabaya - Dhimas Febryant Nursetyo; Dr. Jojok Dwiridotjahjono (Lavish Opulent Education, 2025)
Market segmentation, target market determination, and market positioning are fundamental aspects of marketing strategy that every business owner must consider. Segmentation identifies which markets have the potential to become target markets, thereby enhancing the business. Targeting involves determining the target market through evaluation and development based on the segmentation that has been identified. Positioning refers to the perception or image that a company creates for customers regarding the products or services it provides. Imba Coffee Surabaya is one of the coffee shops in Surabaya that applies segmentation, targeting, and positioning in its marketing. This study aims to observe how Imba Coffee applies STP by analyzing the effectiveness of STP implementation in increasing sales. The type of research used is descriptive research with a qualitative approach. This study also emphasizes the researcher's understanding of how marketing strategies based on the application of STP at Imba Coffee are designed and implemented to increase sales. The type of research used is descriptive research with a qualitative approach.